S1‐guideline atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS). (31st January 2022) - Helbig, Doris; Ziemer, Mirjana; Dippel, Edgar; Erdmann, Michael; Hillen, Uwe; Leiter, Ulrike; Mentzel, Thomas; Osterhoff, Georg; Ugurel, Selma; Utikal, Jochen; von Bubnoff, Dagmar; Weishaupt, Carsten; et al.
Summary: Atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS) are rare cutaneous neoplasms representing histomorphological, genetic as well as epigenetic variants of a disease spectrum. Both tumors typically manifest as nonspecific, often ulcerated, skin‐ to flesh‐colored nodules in chronically sun‐damaged skin of elderly male patients. AFX is a rather well demarcated, often rapidly growing tumor. PDS tumors are poorly circumscribed and are characterized by aggressive infiltrative growth. Fast as well as slow growth behavior has been reported for both tumors. Histologically, both are composed of spindle‐shaped and epithelioid tumor cells with pleomorphic nuclei as well as atypical multinucleated giant cells. Atypical mitoses are common. In contrast to AFX, PDS involves relevant parts of the subcutis and shows areas of tumor necrosis and/or perineural infiltration. Due to the poorly differentiated nature of AFX/PDS (Grade 3), histopathologically similar cutaneous sarcomas, undifferentiated carcinomas, melanomas and other diseases have to be excluded by immunohistochemical analysis. The treatment of choice is micrographically controlled surgery. In cases of AFX, a cure can be assumed after complete excision. Local recurrence rates are low as long as PDS tumors are surgically removed with a safety margin of 2 cm. Metastasis is rare and mostly associated with very thick or incompletely excised tumors; it mainly affects the skin and lymph nodes. Distant metastasis is even more rare. No approved and effective systemic therapy has been established.